2014
DOI: 10.5301/ijao.5000286
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroModel of a System of Electrical Potential Compensation in Extracorporeal Circulation

Abstract: The outcomes confirm the development of parasitic ECs during ECC and that a suppressor system may decrease the potential damage of ECs. Nevertheless, further studies are ongoing in order to investigate the complex mechanisms related to lymphocytes and platelet morphological and physiological chances during triboelectric charges in ECC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that triboelectric effects of the red blood cell membrane, generated through friction in the circulation, can attract bacteria. 64 In studies of the blood microbiome, it has recently been shown that red blood cells contain more potentially pathogenic bacteria than other fractions of the whole human blood. [65][66][67] We established protocols 67 using improved methods for dealing with a) low copies of unknown bacterial DNA, and b) extraction of DNA from difficult sources such as soil and human blood, where acids as well as minerals such as iron create a challenge for more conventional DNA extraction methods.…”
Section: Example 1 -Fibromyalgiamentioning
confidence: 99%
“…It has been suggested that triboelectric effects of the red blood cell membrane, generated through friction in the circulation, can attract bacteria. 64 In studies of the blood microbiome, it has recently been shown that red blood cells contain more potentially pathogenic bacteria than other fractions of the whole human blood. [65][66][67] We established protocols 67 using improved methods for dealing with a) low copies of unknown bacterial DNA, and b) extraction of DNA from difficult sources such as soil and human blood, where acids as well as minerals such as iron create a challenge for more conventional DNA extraction methods.…”
Section: Example 1 -Fibromyalgiamentioning
confidence: 99%
“…It has been suggested that triboelectric effects of the red blood cell membrane, generated through friction in the circulation, can attract bacteria. 64 In studies of the blood microbiome, it has recently been shown that red blood cells contain more potentially pathogenic bacteria than other fractions of the whole human blood. [65][66][67] We established protocols 67 using improved methods for dealing with a) low copies of unknown bacterial DNA, and b) extraction of DNA from difficult sources such as soil and human blood, where acids as well as minerals such as iron create a challenge for more conventional DNA extraction methods.…”
Section: Example 1 -Fibromyalgiamentioning
confidence: 99%